Table of Content - -, (Journal of Educational and Psychological Sciences, 2025)
Table of Content:1. Educational principles derived from the dialogue of the Prophet, may God bless him and grant him peace, with his wives and their applications in the Muslim familyDr. Noura Hammoud Al-Mutairi2. The relationship between Alexithymia and peer attachment among female students of Hail UniversityMs. Bashayr Nawaf Al-Shammari3. Sports activities and their relationship to mental health and academic achievement  among children with autism spectrum disorder from the point of view of specialistsDr. Mersal Abdullah Suleiman Mersal4. The Level of Bullying among Students with Learning Disabilities from the Point of View  of their Parents in the City of MakkahMs. Saliha Hussein Mohammed Alharthi, Co-Prof. Nawal Ahmad Elbadawy Abu Alula5. The effectiveness of cognitive-behavioral therapy for obsessive-compulsive disorder by using remote digital knowledge media in a sample in my extended family (Al-Jazeera State- Sudan)Co-Prof. Bakhita Mohammed zain Ali6. Proposed Quality Standards in the RTI Implementation at the LD programs: Faculty perspectivesMs. Hanan Hussain Al Dukain, Dr. Alwiah Abdullah Alsaggaf7. Family educational care of the blind children and its relationship  to their social adaptationDr.Abdelrahman Gibreel Imam8. Artificial Intelligence in Education: A Future VisionDr. Zohor Mohammed Al-Areeshi
Keywords: Journal of Educational and Psychological Sciences